Axl promotes intracranial aneurysm rupture by regulating macrophage polarization toward M1 via STAT1/HIF-1α - Han, Yongquan; Li, Gaozhi; Zhang, Zeyu; Zhang, Xiaohua; Zhao, Bing; Yang, Hua (Frontiers in Immunology, 2023)
Background Macrophage infiltration and polarization are crucial for the pathogenesis of intracranial aneurysm (IA) rupture. Axl, a receptor tyrosine kinase, is involved in inflammation and efferocytosis in multiple organs. Upregulated soluble Axl in cerebrospinal fluid (CSF) and plasma is correlated with intracranial aneurysm rupture. This study aimed to investigate the role of Axl in IA rupture and macrophage polarization. Methods Male C57BL/6J mice were used to induce IA. The level of Axl from control vessels and unruptured and ruptured IA samples was detected. In addition, the relationship between Axl and macrophages was confirmed. The pathway of Axl-mediated macrophage polarization was explored after IA induction in vivo and in bone marrow-derived macrophages (BMDMs) stimulated by LPS/IFN-γ in vitro. The animals were randomized into three groups and treated intraperitoneally with the vehicle, selective AXL antagonist R428, and recombinant mouse growth arrest-specific 6 (rmGas6) for 21 consecutive days. Then, we evaluated the influence of Axl on IA rupture by administrating R428 to inhibit or rmGas6 to activate the Axl receptor in vivo. Results Compared with that in normal vessels, Axl expression was significantly upregulated in unruptured IA samples. The ruptured IA tissue exhibited significantly higher expression of Axl than the unruptured IA tissue. Axl and F4/80 were coexpressed in IA tissue and LPS/IFN-γ-stimulated BMDMs. R428 treatment significantly reduced the rate of M1-like macrophage infiltration and IA rupture. In contrast, rmGas6 treatment promoted M1 macrophage infiltration and IA rupture. Mechanistically, R428 inhibited the phosphorylation of Axl and STAT1 and the expression of hypoxia-inducible factor-1α (HIF-1α) and decreased the levels of IL-1β, NOS2, and MMP9 in LPS/IFN-γ-stimulated BMDMs. rmGas6 promoted the phosphorylation of Axl and STAT1 and the expression of HIF-1α. In addition, STAT1 knockdown abolished Axl-mediated M1 macrophage polarization. Conclusion The inhibition of Axl reduced macrophage polarization toward the M1 phenotype via the STAT1/HIF-1α signaling pathway and prevented IA rupture in mice. This finding suggests that pharmacological inhibition of Axl might be used to prevent the progression and rupture of IA.